ParkDetect - Early Diagnosing Parkinson's Disease - Ricardo Gabriel da Silva Graça (2013)
Parkinson's disease is one of the most common neurodegenerative disorders of the central nervous system that affects elderly. There are four main symptoms: tremors, rigidity, slow movement and posture instability. Nowadays any type of diagnose for this disorder is done through observation by a health care professional specialized in this area. Therefore it is necessary a method that is simple and efficient for health care professionals of general clinic to use so they decide to forward a possible patient to a specialist. In this context a mobile application where a health care professional can insert values about possible patient's symptoms or the patient himself can realize small test is an interesting challenge. This project has three important phases: development of a smartphone application, use it to gather data from real patients and a control group and testing and selection of a classification algorithm (selecting the relevant data and compare different algorithms) to be inserted in the same application.